The Effect of Work Culture, Compensation, and Innovative Behavior on Employee Job Satisfaction - Nazpi, Nazpi; Ali, Hapzi; Imron Rosadi, Kemas (Siber Journal of Advanced Multidisciplinary, 2023)
The effect of work culture, compensation and innovative behavior on employee job satisfaction is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) work culture has an effect on employee job satisfaction; 2) compensation has an effect on employee job satisfaction; and 3) innovative behavior has an effect on employee job satisfaction.